Penerapan Media Video Animasi Pada Materi Pemanasan Global Untuk Meningkatkan Hasil Belajar Dan Kemampuan Literasi Sains Siswa Kelas XI IPA SMAN Binino - Maria Clarita Lake; Alfons Bunga Naen; Rosenti Pasaribu (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
The purpose of this study was to determine the improvement of learning outcomes and science literacy skills of students by neutralizing animated video media on the subject matter of global warming by conducting experimental research with a pre-experimental design approach. Research with a pre-experimental design approach chosen is one group or one class pretest-posttest (One-Group Pretest-Posttest Design). The sample in this study were X1 Science class students of SMA Negeri Binino, totaling 17 people. The tools used in this study were in the form of lesson plans, animated video media, grids of learning outcomes test questions and students' science literacy skills. The results of this study indicate that the application of animated video media can improve learning outcomes and science literacy skills of students on global warming material. This is seen from the results of the posttest which has increased and the results of the N-Gain Score test calculation on learning outcomes with an average value of 0.42 in the moderate category and the results of the N-Gain Score test on students' science literacy skills with an average value of 0.43 in the moderate category. Based on the research that has been conducted at SMAN Binino and the results obtained, the researcher would like to suggest that in a learning process the use of learning media is very helpful for teachers in conveying learning objectives or material because learning will be more meaningful.